2016
DOI: 10.1038/srep38585
|View full text |Cite
|
Sign up to set email alerts
|

Baseline neutrophil–lymphocyte ratio is associated with baseline and subsequent presence of brain metastases in advanced non-small-cell lung cancer

Abstract: We examined the predictive value of neutrophil–lymphocyte ratio (NLR) by examining their association with the baseline presence and subsequent development of brain metastases in patients with stage IV non-small cell lung cancer (NSCLC). We examined the predictive value of NLR for brain metastasis in 260 stage IV NSCLC. Logistic regression models and competing risk analysis were used to determine the association of NLR with baseline and subsequent presence of brain metastases. Multivariate analysis reveals that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 51 publications
4
21
1
2
Order By: Relevance
“…In our opinion, the pretreatment NLR which was obtained within 1 week before any treatment was more representative of baseline immune status than posttreatment NLR which might be affected by chemotherapy and/or radiotherapy, even though NLR was calculated from blood data 1 month after last chemotherapy or radiotherapy. This was in line with most of studies that showed the low baseline NLR was associated with better survival outcomes [29][30][31][32].…”
Section: Discussionsupporting
confidence: 91%
“…In our opinion, the pretreatment NLR which was obtained within 1 week before any treatment was more representative of baseline immune status than posttreatment NLR which might be affected by chemotherapy and/or radiotherapy, even though NLR was calculated from blood data 1 month after last chemotherapy or radiotherapy. This was in line with most of studies that showed the low baseline NLR was associated with better survival outcomes [29][30][31][32].…”
Section: Discussionsupporting
confidence: 91%
“…In our opinion, the pretreatment NLR which was obtained within one week before any treatment was more representative of baseline immune status than posttreatment NLR which might be affected by chemotherapy and/or radiotherapy, even though NLR was calculated from blood data one month after last chemotherapy or radiotherapy. This was in line with most of studies that showed the low baseline NLR was associated with better survival outcomes [29][30][31][32].…”
Section: Discussionsupporting
confidence: 91%
“…In our opinion, the pretreatment NLR which was obtained within one week before any treatment was more representative of baseline immune status than posttreatment NLR which might be affected by chemotherapy and/or radiotherapy, even though NLR was calculated from blood data one month after last chemotherapy or radiotherapy. This was in line with most of studies that showed the low baseline NLR was associated with better survival outcomes [8,[19][20][21].…”
Section: Discussionsupporting
confidence: 90%